Association between osteoporosis and severe depressive symptoms among postmenopausal women attending tertiary outpatient clinics in Nigeria: a cross-sectional study - Uchenna Cosmas Ugwu; Osmond Chukwuemeka Ene (BMC Women's Health)
Abstract Background/Objectives Osteoporosis and depression are significant, frequently co-occurring conditions in postmenopausal women, particularly in low- and middle-income countries where access to integrated care is limited. This study aimed to examine the association between osteoporosis and severe depressive symptoms among postmenopausal women attending tertiary outpatient clinics in Nigeria and to identify related demographic, clinical, and lifestyle correlates. Methods A hospital-based cross-sectional survey was conducted from July 2024 to May 2025 across 12 purposively selected tertiary outpatient clinics representing all six geopolitical zones of Nigeria. A total of 712 postmenopausal women aged ≥ 45 years (mean age: 60.3 years) were recruited using multistage and convenience sampling. Data were collected via a validated, structured questionnaire; the Osteoporosis and Depression Assessment Questionnaire (ODAQ), which included sociodemographic data, menopausal and clinical history, osteoporosis risk factors, PHQ-9 depression screening, and lifestyle variables. Descriptive statistics and chi-square (χ²) tests were used to analyze the association between osteoporosis and depressive symptoms, with significance set at p ≤ 0.05. Results Severe depressive symptoms were identified in 75.6% of participants. Depression was significantly more common among those with osteoporosis (79.1% vs. 66.5%; χ² = 2.190, p = 0.010) and a history of fractures (87.1% vs. 68.2%; χ² = 5.513, p = 0.012). Other factors associated with higher depressive symptoms included older age (≥ 60 years), late menopause (after age 50), low parity (≤ 5 pregnancies), comorbid chronic conditions (80.4%; p = 0.031), and abnormal anthropometry. Adequate calcium intake was associated with lower depression rates (61.1% vs. 80.9%; p = 0.010). Notably, non-smokers and alcohol users exhibited higher depression rates compared to their counterparts, suggesting possible coping behaviors or reporting biases. Conclusion The findings underscore a strong association between osteoporosis and severe depressive symptoms in Nigerian postmenopausal women, highlighting the urgent need for integrated mental and bone health interventions in tertiary and primary healthcare settings. Screening for depression should be routinely included in osteoporosis management to improve outcomes in aging women. This study supports WHO’s call for integrated non-communicable disease care and offers evidence to inform policy and clinical practice in similar low-resource settings.